2023
DOI: 10.3390/diagnostics13050847
|View full text |Cite
|
Sign up to set email alerts
|

Association of Kinesiophobia with Catastrophism and Sensitization-Associated Symptoms in COVID-19 Survivors with Post-COVID Pain

Abstract: Pain symptoms after the acute phase of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) are present in almost 50% of COVID-19 survivors. The presence of kinesiophobia is a risk factor which may promote and perpetuate pain. This study aimed to investigate variables associated with the presence of kinesiophobia in a sample of previously hospitalized COVID-19 survivors exhibiting post-COVID pain. An observational study was conducted in three urban hospitals in Spain, including one hundred and forty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…assessment was made according to standardized criteria [38]. Next, for statistical analyses, the participants were divided into three groups: I-very low or low exercise performance; II-average or good exercise performance; III-very good or highest exercise performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…assessment was made according to standardized criteria [38]. Next, for statistical analyses, the participants were divided into three groups: I-very low or low exercise performance; II-average or good exercise performance; III-very good or highest exercise performance.…”
Section: Resultsmentioning
confidence: 99%
“…This indirect method of assessing the maximal oxygen uptake uses the established relationship between exercise oxygen uptake and heart rate. The qualitative VO2max assessment was made according to standardized criteria [ 38 ]. Next, for statistical analyses, the participants were divided into three groups: I—very low or low exercise performance; II—average or good exercise performance; III—very good or highest exercise performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinesiophobia, the fear of movement, contributes to the chronicity, persistence, and exacerbation of pain (33). Herrero-Montes et al (34) reported that nearly 57% of patients with post-COVID pain exhibited potential kinesiophobic behavior. Higher kinesiophobia levels are associated with decreased physical activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the participants was 34.70 (SD = 13.584), ranging from 18 to 65 years. The sample size was determined following the guidelines proposed by Austin and Steyerberg (2015) , as also observed in other studies conducted by Collister et al (2023) , Herrero-Montes et al (2023) , Huang et al (2023) , Stepovic et al (2023) , and Yamazaki et al (2023) . Table 1 presents the sociodemographic characteristics of the sample.…”
Section: Methodsmentioning
confidence: 99%